Development of a Web-Based Laundry Information System with Customer Self-Service Using the Rapid Application Development Method - Kevin Alexander Soewandi; Alexander Wirapraja; David Saputra Octadianto Soedargo (Universitas Islam Raden Rahmat, Malang, 2026)
The development of information technology has encouraged various business sectors to digitize their service processes, including the laundry sector. However, Holly Jolly Laundry still uses a manual transaction recording system that has the potential to cause service delays, recording errors, and difficulties in managing customer data. This condition has an impact on low operational efficiency and decreased customer satisfaction levels. Based on these problems, this study aims to design and develop a web-based laundry transaction information system equipped with a self-service feature that allows customers to place orders independently while reducing the potential for recording errors by the admin. The system development method used is Rapid Application Development (RAD), which emphasizes the speed of prototyping and active user involvement in every stage of development, including requirements planning, user design, construction, and cutover. The results show that the developed system is able to accelerate the ordering process, improve the accuracy of transaction recording, and facilitate the admin in managing service data in a more structured and efficient manner. In addition, the self-service feature allows customers to input data directly, thereby reducing the admin's workload and minimizing input errors. Thus, the resulting information system is proven to improve operational efficiency, transaction data accuracy, and service quality at Holly Jolly Laundry.